2014
DOI: 10.1016/j.jallcom.2014.02.005
|View full text |Cite
|
Sign up to set email alerts
|

Electronic structure and magnetism of new scandium-based full Heusler compounds: Sc2CoZ (Z = Si, Ge, Sn)

Abstract: First principles FPLAPW calculations were performed in the framework of Density Functional Theory (DFT), to study the electronic structures and magnetic properties for the new full-Heusler compounds: Sc2CoZ (Z=Si, Ge, Sn). The investigated materials are stable against decomposition, in ferromagnetic configuration and crystallize in the inverse Heusler structures. The half-metallic properties as function of the variation of unit cell volumes are analysed regarding the fourth main group constituent elements. The… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(5 citation statements)
references
References 31 publications
0
5
0
Order By: Relevance
“…[28][29][30]. In Zr 2 CoZ (Z ¼Al, Ga, In, Si, Ge, Sn, Pb) alloys, the atomic magnetic moments of Z atoms are very small (see Table 2) and only make a small contribution to the total spin moment.…”
Section: Resultsmentioning
confidence: 99%
“…[28][29][30]. In Zr 2 CoZ (Z ¼Al, Ga, In, Si, Ge, Sn, Pb) alloys, the atomic magnetic moments of Z atoms are very small (see Table 2) and only make a small contribution to the total spin moment.…”
Section: Resultsmentioning
confidence: 99%
“…Many Co 2 , Mn 2 , Ti 2 , and Sc 2 -Heusler compounds reported in literature are ferromagnetic [15][16][17][18], ferrimagnetic half-metals [19], or spin gapless semiconductors [20]. Among them, Mn 2 CoAl full-Heusler compound crystallizing in Hg 2 CuTiprototype was extensively studied: theoretically investigated, the structure was experimentally verified by XRD and the electron transport characteristics where obtained by a Physical Properties Measurement System (PPMS) on samples cut from ingots.…”
Section: Introductionmentioning
confidence: 99%
“…The DFT calculations showed that the Sc 2 CoSi composition is a ferromagnetic half-metal with a magnetic moment of 0.999 µ B and a lattice constant of 6.28 Å. [25] In this research, the half-metallic, optical and thermodynamic stability behaviors of bulk and thin films surfaces in [001] direction of Sc 2 CoSi have been studied, which has not been done so far. The application of half-metals in the industry is often in the form of thin films, but one of the problems found in Heusler films is the reduction or elimination of spin polarization at their surfaces.…”
Section: Introductionmentioning
confidence: 99%